Long-term spatiotemporal variability of precipitation and its linkages with atmospheric teleconnections in the Yellow River Basin, China. Issue 3 (3rd March 2023) - Wang, Junjie; Chi, Yuning; Shi, Bing; Yuan, Qingyun; Wang, Xia; Shen, Lijun
Abstract: Precipitation is widely considered as a crucial index toward the apprehension of global climate change. Hence, it becomes imperative to explore spatiotemporal patterns and the interlinked factors of precipitation in the basin. In the study, the spatial and temporal variability of precipitation and the individual or integrated effects of various atmospheric teleconnections on precipitation variations are explored in the Yellow River Basin. The total precipitation showed a slightly declining tendency during 1950–2019 and the dependence relationship of precipitation gradient on latitude and longitude is different in various seasons and elevations. The spatiotemporal variability of precipitation is more sensitive to the latitude gradient. For each 1-degree increase in longitude and latitude, the average annual precipitation increases/decreases by 10.73 and 57.24 mm, respectively. Moreover, the precipitation spatiotemporal patterns could be interpreted by four empirical orthogonal functions (EOFs) modes about 71.9% of precipitation variations. The strength of the linkages between various circulation factors and precipitation varied at different time scales. The integrated effects of multiple factors should be taken into consideration in explaining precipitation variability at all time scales. It is expected that the study can be helpful for understanding the internal mechanism of the hydrological cycle in the YRB. HIGHLIGHTS: Long-term spatiotemporal variability of precipitation was explored in the Yellow River Basin. Teleconnection between precipitation and circulation indices was detected. New insights into coupled effects of multiple atmospheric teleconnections on precipitation. Graphical Abstract